2018
DOI: 10.1002/cyto.a.23576
|View full text |Cite
|
Sign up to set email alerts
|

How to Agree on a CTC: Evaluating the Consensus in Circulating Tumor Cell Scoring

Abstract: For using counts of circulating tumor cells (CTCs) in the clinic to aid a physician's decision, its reported values will need to be accurate and comparable between institutions. Many technologies have become available to enumerate and characterize CTCs, thereby showing a large range of reported values. Here we introduce an Open Source CTC scoring tool to enable comparison of different reviewers and facilitate the reach of a consensus on assigning objects as CTCs. One hundred images generated from two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…39 The operator bias in CTC classification can be improved by providing quantitative information of the objects in the thumbnails and can be eliminated by the use of gates with the open-source ACCEPT software (http://github.com/LeonieZ/ ACCEPT). 14,[41][42][43] Further improvements in the classification of CTCs can be obtained through the use of deep learning; 44 however, for its implementation on larger data sets, significant improvements in the software are still needed. Therefore, in this study, we elected to use the original CTC scores of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…39 The operator bias in CTC classification can be improved by providing quantitative information of the objects in the thumbnails and can be eliminated by the use of gates with the open-source ACCEPT software (http://github.com/LeonieZ/ ACCEPT). 14,[41][42][43] Further improvements in the classification of CTCs can be obtained through the use of deep learning; 44 however, for its implementation on larger data sets, significant improvements in the software are still needed. Therefore, in this study, we elected to use the original CTC scores of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Zeune et al. [56] reported that the manual counting for CTCs of prostate cancer and non‐small cell lung cancer on fluorescent images varied among human reviewers and counting platforms, whereas DL‐based CTC recognition was relatively stable with higher accuracy than the average level of human reviewers.…”
Section: Application Of Dl‐based Ai In Tumor Pathologymentioning
confidence: 99%
“…Capture of CTCs and tumorderived DNA samples for genetic, proteomic and other analyses has been termed "liquid biopsy" (26) since simple blood samples, often obtained repeatedly over time, yield information regarding otherwise difficult to access solid tissue tumors. Over the past years, multiple commercial platforms involving negative and positive immune and nonimmune-based identification of leukocyte and tumor antigens, respectively, were used in oncology, and recently efforts are underway to assess agreement across platforms and methods (28). Over the past years, multiple commercial platforms involving negative and positive immune and nonimmune-based identification of leukocyte and tumor antigens, respectively, were used in oncology, and recently efforts are underway to assess agreement across platforms and methods (28).…”
mentioning
confidence: 99%
“…Initial carcinoma CTC assays were immune-based using fluorescent antibodies to antigens widely expressed by epithelial cells, such as cytokeratin and cell adhesion molecules (27). Over the past years, multiple commercial platforms involving negative and positive immune and nonimmune-based identification of leukocyte and tumor antigens, respectively, were used in oncology, and recently efforts are underway to assess agreement across platforms and methods (28). The number of CTCs detected in humans with carcinoma is extremely low, and significant prognostic differences have been attributed to 3 versus 5 CTC/7.5 ml of blood (25,29).…”
mentioning
confidence: 99%